Design and Evaluation of Polyox and Pluronic Controlled Gastroretentive Delivery of Troxipide. (18th November 2014) - Jagdale, Swati C.; Kamble, Shraddha B.; Kuchekar, Bhanudas S.; Chabukswar, Aniruddha R.
Abstract : Objective . Objective of the present work was to develop site-specific gastroretentive drug delivery of Troxipide using polymers Pluronic F127 and Polyox 205 WSR. Troxipide is a novel gastroprotective agent with antiulcer, anti-inflammatory, and mucus secreting properties with elimination half-life of 7.4 hrs. Troxipide inhibits H. pylori -derived urease. It is mainly absorbed from stomach. Methods . 3 2 factorial design was applied to study the effect of independent variable. Effects of concentration of polymer on dependant variables as swelling index, hardness, and % drug release were studied. Pluronic F127 and Polyox 205 WSR were used as rate controlled polymer. Sodium bicarbonate and citric acid were used as effervescent-generating agent. Results . From the factorial batches, it was observed that formulation F5 (19% Pluronic F127 and 80% Polyox 205 WSR) showed optimum controlled drug release (98.60% ± 1.82) for 10 hrs with ability to float >12 hrs. Optimized formulation characterized by FTIR and DSC studies confirmed no chemical interactions between drug and polymer. Gastroretention for 6 hrs for optimized formulations was confirmed by in vivo X-ray placebo study. Conclusion . Results demonstrated feasibility of Troxipide in the development of gastroretentive site-specific drug delivery.